Correlation between Knowledge of Online Learning Methods and Students’ Motivation During the Covid-19 Pandemic - C. Ermayani Putriyanti; Caecilia Titin Retnani; Masruchi; Prihanto (STIKES Ngesti Waluyo, 2022)
The Covid 19 pandemic has many impacts on various aspects of life of the Indonesian people; one of which is education. One crucial change is in learning methods, which shifts from face to face (offline) to online learning methods). Students need to adapt to the changes because some students have never used online learning methods. The shifting learning method could affect students’enthusiasm for learning, particularly for students who have never used this method before. The objective of this study was to determine the correlation between knowledge of online learning method and learning motivation of nursing students. The research design was cross-sectional. The research respondents were 112 nursing students from four universities in Central Java and Yogyakarta, that were taken by stratified random sampling method. The inclusion criteria are Diploma 3 Nursing students, age 18-25 years old, and students who are undergoing online learning. Data were collected using google form questionnaire which has been tested for validity and reliability. The data analysis used were univariate test for respondent characteristics, and correlation test using Spearman Rho. The results show that the characteristics of respondents are mostly at the age of 18-20 years (81.25%), the educational background of high school is 64.3%, and students who are also working are 2.7%. The most widely used application for online learning is Whatsapp (87.5%). The level of student knowledge is mostly good (54.5%), whereas other 33.9% respondenst are having sufficient knowledge, and 11.6% other are lack of knowledge about online learning. While the level of learning motivation is 0% weak motivation, 33.9% moderate motivation and 59% strong motivation. The correlation between knowledge of online learning method and learning motivation is significant, as shown by the p-value of 0.001 (p<0.005). As conclusion, during the Covid 19 pandemic, students who have good knowledge of learning method have significantly strong learning motivation.